Micro-structural evolution of rubber/clay nanocomposites with vulcanization process (eXPRESS Polymer Letters)
Brominated isobutyl-isoprene rubber/clay nanocomposite (BIIRCN) and ethylene-propylene-diene-monomer rubber/clay nanocomposite (EPDMCN) were prepared by melt blending. The micro-structural evolution of these two kinds of rubber/clay nanocomposites (RCNs) with vulcanization process was investigated using wide-angle X-ray diffraction (WAXD) and transmission electron microscope (TEM). The WAXD results revealed that the intercalated structure of organically modified clay (OMC) changed throughout the whole curing process. The intercalated structure kept on changing beyond the vulcanization stage of T90. The interlayer space of intercalated silicate in uncured BIIRCN is larger than that in uncured EPDMCN. However, the intercalated structure for EPDMCN changed by a larger extent than that for BIIRCN during the vulcanization process, and the interlayer space of the intercalated structure is larger in the cured EPDMCN than that in the cured BIIRCN. It was found that the intercalant (i.e., octadecylamine, ODA) for OMC could shorten the scorch time of the curing reaction, and increase the curing rate, which was attributed to the further intercalation during vulcanization. TEM results indicated that the spatial distribution of OMC is much better in BIIR (a polar rubber matrix) than that in EPDM (a non-polar rubber matrix). The changes in spatial dispersion structure during vulcanization for EPDMCN and BIIRCN show different trends. In conclusion, the polarity of the rubber is the determining factor influencing the evolution of both the intercalated structure and the spatial dispersion of clay during vulcanization.